1999
DOI: 10.1002/(sici)1098-2329(199922)18:2<89::aid-adv1>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

The development of laminar morphology in a co-rotating twin screw extruder

Abstract: Laminar morphology of high‐density polyethylene (HDPE)/polyamide‐6 (PA‐6) blends was obtained, for the first time, in a co‐rotating twin screw extruder. The morphology analysis in the interior of the adapter, which connects the extruder with a slit die, revealed that, under specific processing conditions, it is possible to produce layers of PA‐6 in the end of the screw zone of the extruder. The micrographs of the extruded final products showed distributed layers across the sample thickness and along the flow d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…In general, the rheology foundation to produce polymer blend with microlayer structure is the flow of binary phase, in which the melt viscosity and elasticity ratio are the most important 30. We have confirmed that a polymer blend owning the morphology with the plastic as the dispersed phase and the rubber as the matrix is benefit to form the co‐continuous microlayer structure during injection molding 26.…”
Section: Resultssupporting
confidence: 53%
“…In general, the rheology foundation to produce polymer blend with microlayer structure is the flow of binary phase, in which the melt viscosity and elasticity ratio are the most important 30. We have confirmed that a polymer blend owning the morphology with the plastic as the dispersed phase and the rubber as the matrix is benefit to form the co‐continuous microlayer structure during injection molding 26.…”
Section: Resultssupporting
confidence: 53%
“…However, in this study, the domain size in EOR/PP blends was larger than those in other blends, which may be ascribed to viscosity. In general, the rheology foundation to produce polymer blend with microlayer structure is the flow of binary phase, in which melt viscosity and elasticity ratio are the most important parameters . Higher viscosity of the matrix phase can delay the break‐up time after shear deformation, thereby favoring lamellar orientation .…”
Section: Resultsmentioning
confidence: 99%
“…This change in morphology results in a higher tortuosity within the blend which significantly reduces the permeability, and almost achieves the permeability of a coextruded nylon sheet. [1,20,21] Poly(styrene-ran-acrylonitrile), SAN, has excellent grease and chemical resistance as well as high gas barrier properties due to the polarity of the acrylonitrile monomer. [22] For this reason it would make an excellent barrier material within a PE blend.…”
Section: Barrier Polymersmentioning
confidence: 99%
“…[13,17,48,49] If a lamellar morphology is obtained with the polymer blend, barrier properties approach those of a layered material made by coextrusion. [20,21] However, most polymer blends are immiscible and must be compatibilized to form stable blend morphologies. The inherent amine functionality at the chain end of a polyamide makes it very easy to blend with maleic anhydride grafted PE to form a compatibilized polymer blend with a stable morphology.…”
Section: Manuscript Introductionmentioning
confidence: 99%